ANALISIS LIFE CYCLE COST PERKERASAN KAKU DAN LENTUR JALAN PROVINSI (STUDI KASUS: JALAN RAYA PARE – KEDIRI) - Hermastuti, Gita Rizqi; Amudi, Abdiyah (Universitas PGRI Semarang, 2024)
Pare-Kediri Highway is a provincial road which is the main connecting road between Pare and Kediri City. On this road section is often bypassed by vehicles with large loads. However, in existing conditions there is damage that varies. Road planning is generally planned to be used for a certain period of time, for example 10 to 20 years depending on existing transportation needs, in the hope that the road will remain in good condition and suitable for traffic. Road maintenance measures are necessary to ensure good operating conditions throughout the planning period. Maintenance and repair of damaged roads also cost a lot. As a result evaluating road damage and choosing the right type of repair is very important. According to the results of research with the 2017 pavement Design Manual guidelines, flexible pavement thickness was obtained including AC-WC 4 cm, AC-BC 6 cm, AC-Base 16 cm and Class A aggregate foundation layer 15 cm. While the thickness of the rigid pavement using continuous concrete without reinforcement with 30 MPa quality concrete obtained plate thickness of 28.5 cm and a layer of thin concrete foundation (LMC) 10 cm. Based on data processing, the construction cost of flexible pavement amounted to Rp 12,958,812,587.00 while rigid pavement amounted to Rp 30,584,262,345. 00. The Total maintenance cost for flexible pavement is Rp 23,836,678,414.33 while for rigid pavement is Rp 3,208,462,265. 15. So that the results of life cycle cost analysis of this study obtained the total cost during the 20-year life cycle of flexible pavement of Rp 36,795,491,001.33 while rigid pavement of Rp 33,792,724,610. 15. In this case, rigid pavement has a life cycle cost (life cycle cost) which is 8.51% more efficient than flexible pavement.